Peningkatan Kemampuan Literasi Pemanfaatan Simplisia Tanaman Obat Herbal untuk Kesehatan Keluarga: Improvement of Literacy Skills in the Utility of Herbal Simplicia Medicine for Family Health - Purba, Abdul Khairul Rizki; Sakina, Sakina; Hasanatuludhhiyah, Nurina; Fatimah, Nurmawati; Paramitha, Nabilah; Mukhoirotin, Mukhoirotin; Toyib, Muchammad (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Indonesia has a variety of plants with various health benefits. Communities in small linkages such as families, RT, and RW can utilize family medicinal plants (TOGA) to maintain stamina so that immunity remains optimal. Educational efforts to utilize TOGA simplisia were carried out in the form of community service in Sumorame, Candi District, Sidoarjo Regency. A total of 38 participants attended the training. The methods used in this activity include counseling and workshops. The knowledge domain of traditional medicine increased by 47.6 points higher than the pretest. A total of 26 participants (68.4%) stated that they often used TOGA. The reasons for using TOGA include natural remedies (n = 22; 57.9%), maintaining stamina and health (n = 12; 31.6%), and first aid when sick before seeing a doctor (n = 4; 10.5%). During the training, participants mentioned 2 to 6 parts of TOGA with their properties. Participants received information about TOGA and its utilization from social media (15%), and mass media (10-14%). The information sources from academics are still low (3%). The community has the potential to use TOGA which can be considered to maintain health in the long term. They already know its utilization from generations and mass media information. Continuous education by academics and health workers is needed for public health and to drive the economy.